Розгортання мікросервісноі архітектури за допомогою докера - Рєзнік, Я. В. (ХНУРЕ, 2020)
The Face Recognition (FR) is growing as a major research area because of the broad choice of applications in the fields of commercial and law enforcement. Traditional FR methods based on Visible Spectrum (VS) are facing challenges like object illumination, pose variation, expression changes, and facial disguises. Unfortunately these limitations decrease the performance in object identification and verification. To overcome all these limitations, the Infrared Spectrum (1RS) may be used in human FR. So it leads and encourages the researchers for continuous research in this area of FR